2006
DOI: 10.1016/j.exer.2005.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia preconditioning protects corneal stromal cells against induced apoptosis

Abstract: The purpose of this study, was to determine whether hypoxia preconditioning can protect corneal stromal cells from UV stress and cytokine mediated apoptosis. Two models were implemented. First, primary cultured bovine corneal fibroblasts were preconditioned with 0.5-1.5% O2 for 4 hr and stressed with UV-irradiation or stimulation of Fas receptor. Second, bovine eyes were preconditioned with 0.5% O2 for 4 hr and stressed by epithelial scraping to induce anterior keratocyte apoptosis. Cell fate was analyzed at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 53 publications
(42 reference statements)
4
30
0
Order By: Relevance
“…Other possible pharmacological approaches to managing CTK include doxycycline, which has been shown to decrease the expression of interleukin 1 and tumour necrosis factor-α, which are proven to induce keratocyte apoptosis, although no studies have been performed to test its effect on CTK 16. Topical vitamin E application after photorefractive keratectomy has also been shown to decrease keratocyte apoptosis 16 17.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible pharmacological approaches to managing CTK include doxycycline, which has been shown to decrease the expression of interleukin 1 and tumour necrosis factor-α, which are proven to induce keratocyte apoptosis, although no studies have been performed to test its effect on CTK 16. Topical vitamin E application after photorefractive keratectomy has also been shown to decrease keratocyte apoptosis 16 17.…”
Section: Discussionmentioning
confidence: 99%
“…22 The corneal stromal cells (obtained from remnant donor tissue after corneal transplantation) were harvested at or before 7 days after death. Descemet's membrane and epithelium were removed using forceps and an ophthalmic knife.…”
Section: Isolation and Culture Of Human Corneal Stromal Cellsmentioning
confidence: 99%
“…42 However, Xing et al reported that hypoxia protects corneal stromal cells against induced apoptosis. 43 Miechia et al reported that an increase of functional laminin-5 protein in the extracellular matrix of hypoxic corneal epithelial cells promotes apoptosis. 44 Kallinikos et al reported also keratocyte loss resulting from contact lens use and they suggested that keratocyte loss is associated with mechanical, cytokine-mediated and hypoxic effects.…”
Section: Discussionmentioning
confidence: 99%